2009
DOI: 10.1038/bmt.2009.230
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of thrombotic microangiopathy after allogeneic hematopoietic cell transplantation with high-dose or nonmyeloablative conditioning

Abstract: The role of conditioning intensity on occurrence of thrombotic microangiopathy (TMA) after allogeneic hematopoietic cell transplantation (HCT) has remained unclear thus far. Here, we retrospectively compared the incidence of TMA in patients given allogeneic hematopoietic stem cells after either nonmyeloablative (n ¼ 176) or high-dose (n ¼ 111) conditioning. The 1-year cumulative incidence of TMA was 13% in nonmyeloablative recipients versus 15% in high-dose conditioning recipients (P ¼ 0.5). In multivariate Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 25 publications
(34 reference statements)
3
58
0
1
Order By: Relevance
“…These results are concordant with other reports of close associations between TA-TMA and GVHD. 3,5,8,[10][11][12]14 This may be because, during engraftment, donor T lymphocytes first encounter host endothelial cells. 4 Moreover, increased levels of coagulation factors (Von Willebrand factor, soluble thrombomodulin), inflammatory cytokines (TNF-a, IL-1, IFN-g, IL-8) associated with cell injury or adhesion molecules (sVCAM-1) have been reported in the setting of acute GVHD, as well as circulating endothelial cells and microparticles to favor platelet aggregation and microthrombosis expressing markers of endothelial activation (CD62, anexin V).…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are concordant with other reports of close associations between TA-TMA and GVHD. 3,5,8,[10][11][12]14 This may be because, during engraftment, donor T lymphocytes first encounter host endothelial cells. 4 Moreover, increased levels of coagulation factors (Von Willebrand factor, soluble thrombomodulin), inflammatory cytokines (TNF-a, IL-1, IFN-g, IL-8) associated with cell injury or adhesion molecules (sVCAM-1) have been reported in the setting of acute GVHD, as well as circulating endothelial cells and microparticles to favor platelet aggregation and microthrombosis expressing markers of endothelial activation (CD62, anexin V).…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 99%
“…2 The exact pathophysiology of TA-TMA remains unclear, but a variety of potential risk factors have been suggested. 1,3,5,8,[10][11][12][13][14] The use of TAC plus SIR as GVHD prophylaxis has been associated with an increased incidence of TA-TMA, which ranges from 10.8-55%, the latter in patients who received BU plus CY as part of their conditioning regimen. [17][18][19]21,22 In a recent phase II multicenter prospective trial conducted by our group, including some of the patients in this study, no differences were observed in the incidence of TA-TMA when TAC/SIR was compared with patients included in a prior prospective trial using CYA-mycophenolate (the overall incidences of TA-TMA were 10% and 6%, respectively).…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In good agreement with the literature, one of the strongest predictors for TA-TMA was aGvHD grades II-IV. 5,7,10,11,18,32 The role of calcineurin inhibitors and mammalian target of rapamycin inhibitors in the pathogenesis is well established. 2-4 Several publications indicated that the risk of TA-TMA was substantially higher with the combination of TAC and sirolimus.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the exact pathophysiology remains unclear, endothelial dysfunction with platelet activation and formation of platelet-rich thrombi in the microcirculation are regarded as key elements, leading to platelet consumption, mechanical damage to red blood cells and secondary organ damage. 2, 3 The role of predisposing risk factors has been addressed, 2,4-6 such as female gender, 7,8 older age, 9,10 lymphoid malignancy, 11 unrelated donor, 7,10 HLA mismatch, 9 conditioning and immunosuppressive regimens, 7,[10][11][12][13][14][15][16] infections, 3,9,11,17 acute GvHD (aGvHD) 7,[10][11][12]17,18 and ABO incompatibility. 19 Acquired idiopathic thrombotic thrombocytopenic purpura (TTP) also belongs to the family of thrombotic microangiopathies.…”
Section: Introductionmentioning
confidence: 99%